Pilot-Scale Cultivation of the Snow Alga Chloromonas typhlos in a Photobioreactor - Schoeters, Floris; Spit, Jornt; Azizah, Rahmasari Nur; Van Miert, Sabine (Frontiers in Bioengineering and Biotechnology, 2022)
The most studied and cultivated microalgae have a temperature optimum between 20 and 35 °C. This temperature range hampers sustainable microalgae growth in countries with colder periods. To overcome this problem, psychrotolerant microalgae, such as the snow alga Chloromonas typhlos, can be cultivated during these colder periods. However, most of the research has been done in the laboratory. The step between laboratory scale and large-scale cultivation is difficult, making pilot scale tests crucial to gather more information. Here we present a successful pilot scale growth test of C. typhlos. Seven batch mode growth periods were compared during two longer growth tests in a photobioreactor of 350 L. We demonstrated the potential of this alga to be cultivated at colder ambient temperatures. The tests were performed during winter and spring time to compare ambient temperature and sunlight influences. The growth and CO2 usage were continuously monitored to calculate the productivity and CO2 fixation efficiency. A maximum dry weight of 1.082 g L-1 was achieved while a maximum growth rate, maximum daily volumetric and areal productivities of 0.105 d-1, 0.110 g L-1 d-1 and 2.746 g m-2 d-1, respectively, were measured. Future tests to optimize the cultivation of C. typhlos and production of astaxanthin, for example, will be crucial to explore the potential of biomass production of C. typhlos on a commercial scale.